2012
DOI: 10.5740/jaoacint.cs2011_18
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Myo-Inositol (Free and Bound as Phosphatidylinositol) in Infant Formula and Adult Nutritionals by Liquid Chromatography/Pulsed Amperometry with Column Switching: First Action 2011.18

Abstract: Myo-inositol is a 6-carbon cyclic polyalcohol also known as meso-inositol, meat sugar, inosite, and i-inositol. It occurs in nature in both free (myo-inositol) and bound (inositol phosphates and phosphatidylinositol) forms. For the determination of free myo-inositol, samples are mixed with dilute hydrochloric acid to extract myo-inositol and precipitate proteins, diluted with water, and filtered. For the determination of myo-inositol bound as phosphatidylinositol, samples are extracted with chloroform, isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is synthesized in only a few organs such as the testes, kidney and brain [1,2]. MI is a primary component of living cells, serving as precursor for inositol phosphates, phosphatidylinositol (PI) and phosphatidylinositol phosphate (PIP) lipids [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is synthesized in only a few organs such as the testes, kidney and brain [1,2]. MI is a primary component of living cells, serving as precursor for inositol phosphates, phosphatidylinositol (PI) and phosphatidylinositol phosphate (PIP) lipids [3].…”
Section: Introductionmentioning
confidence: 99%
“…Myo-inositol (MI) is a six-carbon, cyclic polyalcohol that exists in many foods and organisms (1). The MI levels are highest in fruits, beans, grains, and nuts (2), and it has been estimated that a mixed North American diet provides human adults with approximately 1 g/day of MI (3).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported only one example of meso ‐inositol‐based star macromolecule preparation by ATRP, notwithstanding this reaction gave a core with five rather than the expected six 2‐bromoisobutyric ATRP initiating sites, leaving one of the hydroxyl functional group underivatised. meso ‐Inositol is a 6‐carbon cyclic polyalcohol, an isomer of glucose also known as myo ‐inositol, meat sugar, inosite, and i ‐inositol . It exists as nine stereoisomers, seven of which are optically inactive or meso.…”
Section: Introductionmentioning
confidence: 99%
“…It exists as nine stereoisomers, seven of which are optically inactive or meso. It occurs in nature in both free ( myo ‐inositol) and bound (inositol phosphates and phosphatidylinositol) forms . Free of phosphate form is a member of the vitamin B complex, formerly vitamin B 8.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation